The definition of digital shadow economy - Remeikiene, Rita; Gaspareniene, Ligita; Schneider, Friedrich Georg (Technological and Economic Development of Economy, 2018)
Considering the lack of the scientific studies on the selected topic, the authors of this article raise the aim to set up the definition of digital shadow economy and identify its distinctive features and channels. Thus far, the studies on illegal digital activities have covered ambiguous interpretations of digital shadow economy that incorporated both criminal and economic aspects of the activities performed. The results of the empirical research have enabled to formulate the definition of digital shadow economy that refers to illegal activities, such as digital service provision and sales of goods/services online, when operating exceptionally in digital space, the entities violate the existent legal norms and regulations with a pursuit of illegal mutual interest and material benefits. The newly formulated definition of digital shadow economy has served as a corner-stone for identification of the distinctive features and channels of this phenomenon. Hence, the results of the research may make a significant and weighty contribution to the development of the theory of economics and may raise the awareness of what the phenomenon of digital shadow economy implies.First published online: 09 Jan 2017